Does Qualification Count? The Effect of Teachers’ Professional Qualifications on their Efficacy in Teaching - Adusei, Opoku; Segbefia, Samuel Kwabla; Djan, Alexander Kwafo; Sarpong, Ama Boatemah; Salakpi, Raymond Kwaku (International Journal of Rehabilitation and Special Education (IJRSE), 2022)
A cross-sectional survey was used to investigate the relationship between the professional credentials held by educators and the calibre of training they deliver. A questionnaire with 12 questions was distributed to 154 senior high school instructors from 20 different senior high schools. The study’s conclusions showed that instructors had a very high level of efficacy. According to the findings of a one-way analysis of variance (ANOVA) test about teacher qualifications, there was no statistically significant difference between the means of the six different groups of teacher professional credentials on teacher efficacy. According to the findings of a one-way analysis of variance (ANOVA) test about teacher qualifications, All Ashanti Region teachers are strongly encouraged to participate in ongoing professional development activities. This is since it is among the most crucial strategies to help teachers feel like they are doing a good job and have faith in their own talents as educators.